Catalisadores com estrutura do tipo perovskitas PrCo1-xNixO3 para produção de gás de síntese - Dias, Eduarda Cristina Caixeta (Universidade Federal de São Carlos, 2017)
Energy is an essential component for a country's development. Since Brazilians’ main energy source is the oil and it has limited reserves, an alternative is needed for a synthesis of fuels throughout other raw materials, such as natural gas, which is abundant in nature and rich in methane. Methane gas is the main precursor for synthesis gas formation, a mixture of CO and H2 that can generates various synthetic compounds such as gasoline, methanol, hydrocarbons and others. This gas mixed with carbon dioxide, which are the two main greenhouse gases, reacts in the presence of a catalyst forming the synthesis gas through the dry reforming. In this context, several studies are being carried out to find a high catalyst conversion, high selectivity for CO and H2, low cost, and mainly resistance to the carbon deposition; which is the main cause of deactivation in this type of catalyst. A family of elements that may contain containing responses to such problems is perovskite oxides showing as a general formula ABO3, which in latter A are the rare earths, alkaline earths or alkaline; and B are the transition metals. In this project they were synthesized with the type of perovskite PrCoO3 with the insertion of the nickel in the structure forming oxides of formula PrCo1-xNixO3. The samples of catalysts were characterized by X-ray diffraction, specific surface area (BET), temperature programed reduction (TPR), X-ray fluorescence (FRX), thermogravimetric analysis (ATG) and thermo differential analysis (DTA). Its catalytic activity was tested in the range of 500 to 800 °C, verifying the results of progressive conversion as the nickel content in the structure increases. The results showed conversions up to 72%, yielding 84,7% for CO and 38, 8% for hydrogen, therefore a ratio of H2 / CO ≈ 1:2. Stability analyzes indicated that the catalysts remained stable, without loss of activity in the time of 8 h. Also it was observed that cobalt assists in the inhibition of carbon formation, minimizing the deactivation.
Keywords: Produção de gás de síntese; Reforma seca do metano; Perovskita; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA